Novel lower-extremity dexterity assessment for Parkinson's disease: validation against measures of arm dexterity and general mobility. Issue 2 (16th January 2023) - Kuhman, Daniel; Edwards, Lloyd J.; Walker, Harrison; Hurt, Christopher P.
Abstract: Purpose: To establish criterion and construct validity of a novel, clinically feasible assessment of lower-extremity dexterity for PD patients. Methods: Thirty-three PD patients performed a unilateral lower-extremity dexterity task "off" and "on" dopaminergic medications with each leg. The task involves iteratively tapping targets with the foot in a specified pattern, and the measured outcome is the time to complete the movement sequence, with longer times indicating worse performance. We correlated leg movement time with standard, validated measures of gait (comfortable and maximal walk speeds), general mobility (timed up and go), upper-extremity dexterity (9-Hole Pegboard), and elements of the Unified Parkinson Disease Rating Scale (MDS-UPDRS). Results: We found significant relationships between lower extremity dexterity and each of these tasks "off" and "on" medications. Task performance also captures known features of PD, including dopamine-mediated improvement in performance and asymmetrical symptom presentation. Conclusions: This task provides a simple assessment of lower extremity function that correlates with validated measures of dexterity, gait, and mobility. It provides objective, continuous data, is inexpensive, requires little technical expertise/equipment, has a small physical footprint, and can be administered quickly. These features increase the feasibility of implementing this assessment tool in clinical settings. Implications for rehabilitation: We introduce a novel task that captures lower extremity dexterity in individuals with Parkinson's disease (PD). The task is validated against gold standard measures of upper extremity dexterity, gait, and general mobility. Performance on the task is sensitive to known features of PD, including dopamine-mediated improvements and asymmetrical symptom presentation. The task is easy to implement and provides higher quality data compared to other common clinical assessments (e.g., MDS-UPDRS).